How trees and people can co- adapt to climate change: reducing vulnerability through multifunctional agroforestry landscapes - Noordwijk, Meine van; Hoang, Minh Ha; Neufeldt, Henry; Öborn, Ingrid; Yatich, T. (World Agroforestry Centre, 2011)
This book focuses on the relationship between climate-change adaptation, rural development and the roles of trees and agroforestry. Rewards' schemes for environmental services (RES) in multifunctional landscapes, which provide incentives for maintaining or restoring multifunctionality, will contribute to a likely reduction in vulnerability to climate change. Rewards may well be an efficient and fair way of investing international funds in climate-change adaptation. The voluntary, conditional and pro-poor aspects of RES will also help to bring the voice of grassroots stakeholders into international and national decision-making processes on how to deal with climate change. That can ensure realism and efficiency in climate-change adaptation, which is yet another strand to be integrated in rural development programs. The argument for such an approach is built on the underlying concepts of climate change, rural livelihoods and multifunctionality of landscapes, as well as the specific roles of trees and farmers as providers of environmental services in agricultural landscapes. However, trees themselves are vulnerable to climate change and co-adaptation is needed and is possible.